Implementasi Model Pembelajaran Kooperatif pada Mata Pelajaran Fiqih di Madrasah Tsanawiyah Negeri 6 Sragen - Mujoko HS; Ngatmin Abbas; Sholikhatun Nisaa; Nisa’ Nur Habibah Miftahul Jannah (CV. Creative Tugu Pena, 2024)
The implementation of Kurikulum Merdeka (Freedom Curriculum) in Indonesia encourages innovation in learning methods, including in Fiqh subjects at the Madrasah Tsanawiyah level. The cooperative learning model emerges as a potential approach to enhance students' conceptual understanding and applicative skills, as well as develop the Pancasila Learner Profile. This study aims to analyze the implementation of the cooperative learning model in Fiqh subjects at MTs Negeri 6 Sragen within the framework of Kurikulum Merdeka, identify challenges and supporting factors, and evaluate its impact on conceptual understanding, applicative skills, and the development of the Pancasila Learner Profile.This research employs a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with teachers and students, and analysis of learning documents. Thematic analysis was conducted with source triangulation to ensure validity. Results: The implementation of the cooperative learning model in Fiqh subjects at MTs Negeri 6 Sragen shows a significant increase in students' active engagement and conceptual understanding of Fiqh material. Key challenges include time constraints and diversity in student abilities, while supporting factors encompass school management support and teacher training. Positive impacts are evident in the enhancement of students' applicative skills in daily life contexts and the strengthening of character in line with the Pancasila Learner Profile, particularly in aspects of cooperation and critical reasoning.